KARAKTERISTIK HUMOR PADA BUKU HUMOR GELITIK KETEK PENGUASA KARYA C. SURYA KELANA: KAJIAN WACANA - Firdaus, Welly (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
The background of the study is based on the humour in the society, in traditional way as well as in modern way. Humour is common to everybody because humour exists in human life. The function of humour is as a means of information and entertainment. As a means of information, humour can deliver the intended message. As a means of entertainment, humour expresses fun effect carrying laught and smile. Therefore, a book of humour collection is a right means to be entertainment. This study focused on humour in the book collection entitled “Humor Gelitik Ketek Penguasa” written by C. Surya Kelana. The methodology of this study was descriptive qualitative study. The data of the study were the characteristics of humour discourse, the function of humour discourse, and the language style of humour discourse in “ Humor Gelitik Ketek Penguasa” written by C. Surya Kelana. The data is analyzed using descriptive qualitative approach.